Insight into the formation of trumpet and needle-type leaf in Ginkgo biloba L. mutant - Tang, Fang; Sun, Pengbo; Zhang, Qian; Zhong, Fengwei; Wang, Ying; Lu, Mengzhu (Frontiers in Plant Science, 2022)
Leaf type of a plant determines its photosynthetic efficiency and adaptation to the environment. The normal leaves of modern Ginkgo biloba which is known as a ‘living fossil’ in gymnosperm are evolved from needle like to fan-shaped with obvious dichotomous venation. However, a newly discovered Ginkgo variety ‘SongZhen’ have different leaf types on a tree, including needle-, trumpet-, strip-, and deeply split fan-shaped leaves. In order to explore the mechanism in forming these leaf types, microscopy of different leaf types and transcriptome analysis of apical buds of branches with normal or abnormal leaves were performed. We found that the normal leaf was in an intact and unfolded fan-shape, and the abnormal leaf was basically split into two parts from the petiole and each exhibited different extent of variation. The needle-type leaves were the extreme having no obvious palisade and spongy tissues and the phloem cells were scattered and surrounded by xylem cells, while the trumpet-type leaves with normal vascular bundles curled inward to form a loop from abaxial side to adaxial side. The other type leaves had the characteristics among needle-, trumpet-type or normal leaves. The transcriptome analysis and quantitative PCR showed that the genes related to abaxial domain were highly while adaxial domain promoting genes were decreasingly expressed in abnormal-type leaf (ANL) buds and abnormal leaves, which might lead to the obvious abaxialized leaves of ‘SongZhen’. In addition, the low expression of genes related to leaf boundary development in ANL buds indicated that single or double-needles (trumpets) leaves might also be due to the leaf tissue fusion. This study provides an insight into the mechanism of the development of the abnormal leaves in ‘SongZhen’ and lays a foundation for investigating the molecular mechanism of the leaf development in gymnosperms.